Pneumocephalus following labour epidural analgesia, a rare case report - Rafiq, Shagufta; Abbasher, Ibrahim; Anwar, Sadia; Ahmad, Ammara; Aziz, Bushra; Denona, Branko (Clinical Journal of Obstetrics and Gynecology, 2021)
The lumbar epidural analgesia is commonly used for labour analgesia. The “loss of resistance to air” LORA technique is commonly used for recognition of epidural space. One of the rare complications of this technique is Pneumocephalus (PC). We want to present a case of Pneumocephalus which the mother developed during epidural analgesia in labour. The patient complained of severe headache immediately after attempt at epidural catheter insertion. The symptoms progressively worsened following delivery. A postnatal anaesthetic review was performed and an urgent CT scan of the brain was arranged that showed pneumocephalus. A conservative management pathway was followed with liberal analgesia, oxygen inhalation and keeping the patient mostly in supine position. Her symptoms regressed in severity over the next three days and subsided after one week. We believe that the amount of air used for LORA should be minimized; LORA should not be used after dural puncture and the use of normal saline would alleviate the risk.